Nilai-nilai Pendidikan di dalam Ayat-ayat Seruan “ياأيهاالنّاس” (Wahai Manusia) - Rijal, Muhammad Khairul; Nasir, Muhammad (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
Exploring, studying and practicing the values contained in the Qur'an is a must for every Muslim. Al-Qur'an is an ocean of knowledge that will never run out to continue to be studied and the values contained therein to be practiced in everyday life. In this study the researcher focused on the educational values contained in the verses starting with “ياأيهاالنّاس”, which if we discuss and study, we will find so many educational values contained in these verses including the values of faith, morals and good manners, as well as social values that are very important to be learned and practiced by Muslims to become pious individually and socially. The purpose of this study is to discuss more deeply the educational values contained in the verses starting with “ياأيهاالنّاس”. The research approach used is to collect verses that begin with the “ياأيهاالنّاس”, then draw conclusions about the educational values contained therein through literacy studies or literature by referring to classical and contemporary Tafsir books and books education.